Handbook of research on information management for effective logistics and supply chains - Jamil, George Leal 1959-; Soares, António Lucas; Pessoa, Cláudio Roberto Magalhães (Advances in logistics, operations, and management science (ALOMS) book series, 2017)
"This book highlights strategies, tools, and skills necessary for supply management within organizations and companies, featuring best practices and empirical research within the field"--